Congestive Hepatopathy: A Case of Fontan-Associated Liver Disease and Review of Literature. Issue 6 (November 2022) - Gosse, Matthew D.; Bosch, Dustin E.
Abstract: We describe a case of congestive hepatopathy due to altered circulation with a Fontan procedure. Congestive hepatopathy is characterized microscopically by sinusoidal dilation and congestion, interstitial edema, and hepatocyte atrophy. Congestive hepatic fibrosis typically exhibits pericentral pattern fibrosis at an early stage, progressing to bridging fibrosis and cirrhosis. Fibrosis scoring systems have recently been described for Fontan-associated liver disease and congestive heart disease–associated hepatopathy. The clinical differential diagnosis for congestive hepatopathy is broad and includes right-sided heart failure ("cardiac hepatopathy"), hepatic vein obstruction (such as Budd-Chiari syndrome), and intrahepatic vessel or sinusoidal obstruction (such as sinusoidal obstructive syndrome). Treatment of congestive hepatopathy is primarily directed toward the etiology of congestion.